The Higher Education System in Argentina. Networks, Genealogies and Conflicts - Santos Sharpe, Andrés Ignacio (2015)
The present manuscript aims to identify the genealogies, understood in a Foucaultian perspective, which leads to the actual Higher Education System in Argentina, by distinguishing how series of events are organized, distributed, organized in terms of institutional relations, signifying chains in the social amalgam and educational networks. This analysis will allow understanding the hierarchical relationships between higher education institutions and how the differences on cultural and curricular traditions and history also motivate (though not impose) the differences on the students and on policies. Finally, it is as well an accurate description of the Higher Education System in Argentina with a strong emphasis on universities.